Antiviral Activity of Various Glycoside Compounds - Al Azzahra, Yunita; Muchtaridi, Muchtaridi; Yusuf, muhammad (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Glycoside compounds consist of several groups of important compounds, such as flavonoids and alkaloids. Sometimes the glycosidic residues in glycoside compounds have an important role in their activity, but some can only increase their pharmacokinetic parameters. However, recent developments in molecular glycobiology have gained a greater understanding of the activity of aglycones vs. glycosides. Several glycoside compounds, such as flavonoid glycosides and Cardiac glycosides, have been known to have antiviral activity, including against Herpes Simplex Virus, Influenza, and Human Immunodeficiency Virus. Still, until now, the potential for various Glycoside compounds as antivirals have not been widely studied, although many biologically active compounds are in the form of glycosides. Further studies regarding the antiviral activity of this glycoside compound are needed to determine the possibility of this compound as an alternative for treating diseases caused by viruses.Keyword : flavonoid glikosida, cardiac glikosida, HSV, Influenza, HIV